A new species of Neoperla (Plecoptera: Perlidae) from the southern region of the Russian Far East - Teslenko, Valentina A. (Zootaxa, 2012)
A new species of Plecoptera, Neoperla zhiltzovae sp. n., from the southern region of the Russian Far East is described and illustrated.